Microstructural and mechanical characterization of additively manufactured parts of maraging 18Ni300M steel with water and gas atomized powders feedstock - Peinado, Gabriel; Carvalho, Cauê; Jardini, André; Souza, Eduardo; Avila, Julián Arnaldo [UNESP]; Baptista, Carlos (Springer Nature, 2024)
The demand for manufacturing components with complex geometries, good mechanical properties, and material efficiency has surged across various industries, encompassing aerospace, military, nuclear, and naval sectors. Laser powder bed fusion (LPBF), as an additive manufacturing (AM) process, has emerged as a promising method for producing ultra-high mechanical strength alloys, like maraging 300 steel (18Ni300M). However, in numerous studies in the literature concerning the effects of processing parameters on the properties of 18Ni300M steel parts fabricated through LPBF, limited attention has been given to the influence that powder atomization methods may exert on the final properties of these parts. This article investigated the effect of gas atomization (GA) and water atomization (WA) processes on the microstructure of 18Ni300M steel powders and the mechanical properties, microstructure, and chemical composition of LPBF-produced parts. The results revealed significant distinctions in the morphology, aggregation degree, and particle size distribution between the GA and WA powders, which directly influenced the microstructure and affected the amount of defects in LPBF-produced parts. Despite the similar mechanical response found in the WA and GA specimens in the elastic region, the samples produced with the WA batch presented a brittle behavior with a ductility of only 4.06%, whereas the GA parts had an elastoplastic behavior with an elongation of 11.52%. The bulks from the WA batch produced in the LPBF process were compromised due to powder contamination with oxygen, which increased gas porosity and effected fragile oxide particles visible on the fracture surface.
Keywords: Additive manufacturing; Laser powder bed fusion; Maraging steel; Mechanical properties; Microstructural characterization; Powder atomization